Therapeutic use of cannabis in treatment for pain in oncology in Colombia (2015)
The purpose of this test is to answer the question: what are the benefits of medicinal cannabis use in treatments for cancer patients in the country? doing a preliminary inquiry into their uses through history, his transcendence in Latin America and especially Colombia , where its use has been more with recreational purpose and not medicinal , also perform an analysis of the costs of treatment in cancer patients , treatments against the use of cannabinoids , finally determining the economic viability both as a therapeutic .